1979
DOI: 10.21273/hortsci.14.6.713
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethephon and Gibberellic Acid on Thinning Peaches1

Abstract: Fruit retention on several cultivars of peach (Prunus persica (L.) Batsch) was reduced when (2-chloroethyl phosphonic acid (ethephon) at 37.5 to 150 ppm was applied during fruit stage I and the beginning of stage II. Leaf yellowing and early drop as well as gummosis of branches and fruits frequently occurred as side effects. Simultaneous application of gibberellic acid (GA3) at 50 to 100 ppm significantly reduced or eliminated the undesirable side effects of ethephon without altering the thinning response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1980
1980
1981
1981

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Severe reductions in fruit size on poorly thinned trees will occur in ex tremely dry seasons. Numerous materials have been used for chemical thinning of peaches but none have provided consist ent, acceptable results on all cultivars (2,4,5,6,7,8,9,10). Byers (3) found that the thinning response with CGA 15281 varied with cultivar, timing, concentra tion, and year.…”
mentioning
confidence: 99%
“…Severe reductions in fruit size on poorly thinned trees will occur in ex tremely dry seasons. Numerous materials have been used for chemical thinning of peaches but none have provided consist ent, acceptable results on all cultivars (2,4,5,6,7,8,9,10). Byers (3) found that the thinning response with CGA 15281 varied with cultivar, timing, concentra tion, and year.…”
mentioning
confidence: 99%